Innovativeness As A Tool For Development Of Competitive Advantage For The Enterprise In XXI Century (Research Bulletins of the Faculty of Economic Sciences, 2017)
In the conditions of a rapidly changing environment, the building of competitive advantage based on innovativeness gives enterprises new opportunities and possibilities (for survival and development). Innovativeness in the ability and motivation to create and implement innovations is their absorption. Development potential has an impact on the enterprise’s innovativeness: material resources and capital in the form of people. This article explains the concept of innovation and innovativeness, as well as the essence of competitiveness and the role of human capital in supporting the innovativeness. Furthermore, this work emphasizes the importance of innovativeness as an important determinant, which shapes the level of competitiveness in the enterprise.
Keywords: innovations; enterprise; competitive advantage; competition; competitiveness